Dificultades del lenguaje oral en niños y niñas de primer año de educación básica de la escuela Juan Montalvo de la ciudad de Pasaje 2014 – 2015. - Huanga García, Yomary Elizabeth (2015)
The development of this thesis titled ORAL LANGUAGE DIFFICULTIES IN CHILDREN FIRST YEAR OF BASIC EDUCATION SCHOOL JUAN MONTALVO CITY PASSAGE. 2014 – 2015 Consists in an investigative, diagnostic and purposive work, it is oriented to identify the incidence in the oral language difficulties in the learning of children in the first year of basic education, for this reason i developed a methodological process based on inductive, deductive, descriptive statistical and hypothetical methods, about the handling of techniques, were used interviews, surveys and an observation test.